2018
DOI: 10.1186/s11671-018-2438-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Hydrogen Evolution by Loading Cd0.5Zn0.5S QDs onto Ni2P Porous Nanosheets

Abstract: Ni2P has been decorated on CdS nanowires or nanorods for efficient photocatalytic H2 production, whereas the specific surface area remains limited because of the large size. Here, the composites of Cd0.5Zn0.5S quantum dots (QDs) on thin Ni2P porous nanosheets with high specific surface area were constructed for noble metal-free photocatalytic H2 generation. The porous Ni2P nanosheets, which were formed by the interconnection of 15–30 nm-sized Ni2P nanoparticles, allowed the uniform loading of 7 nm-sized Cd0.5Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Moreover, single‐phase CdS QDs are not photostable and photocorrosion may take place during photocatalysis. Diverse approaches implemented to overcome these issues include forming a heterostructure of CdS QDs with other semiconductors, polymers, and/or surface loading of noble‐metal cocatalysts . Kandi et al.…”
Section: Introductionsupporting
confidence: 92%
“…Moreover, single‐phase CdS QDs are not photostable and photocorrosion may take place during photocatalysis. Diverse approaches implemented to overcome these issues include forming a heterostructure of CdS QDs with other semiconductors, polymers, and/or surface loading of noble‐metal cocatalysts . Kandi et al.…”
Section: Introductionsupporting
confidence: 92%
“…From Figure D, we can see that the XPS spectra of Cu 2p can be divided into two independent peaks, which belong to 933.1 eV (Cu 2p 3/2 ) and 953.0 eV (Cu 2p 1/2 ) of the following two groups . Figure E shows the binding energy spectrum of P 2p, and the peak value of 134.2 eV corresponds to the surface oxidized copper phosphide . Figure F is the XPS map of Zr 3d.…”
Section: Resultsmentioning
confidence: 94%
“…The results demonstrated that 0.2 mg mL −1 Ni‐Py‐COF was the optimized dosage under our test conditions (Figure S24). The HER yields presented downtrend when the content of Ni‐Py‐COF increased, which may be attributed to the shading effect that the utilization of light reduced as the dispersion concentration of COFs in the solvent increased [23] …”
Section: Methodsmentioning
confidence: 99%
“…The HER yields presented downtrend when the content of Ni-Py-COF increased, which may be attributed to the shading effect that the utilization of light reduced as the dispersion concentration of COFs in the solvent increased. [23] The apparent quantum efficiency (AQE) of Ni-Py-COF was calculated to quantify the photocatalytic activity for hydrogen evolution over the spectral distribution. The AQE, as a function of incident light wavelength, was measured using three different bandpass filters with central wavelengths of 420, 520 and 600 nm.…”
mentioning
confidence: 99%